2021
DOI: 10.1098/rsos.210180
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone signal and stability covary with fitness

Abstract: If sexual signals are costly, covariance between signal expression and fitness is expected. Signal–fitness covariance is important, because it can contribute to the maintenance of genetic variation in signals that are under natural or sexual selection. Chemical signals, such as female sex pheromones in moths, have traditionally been assumed to be species-recognition signals, but their relationship with fitness is unclear. Here, we test whether chemical, conspecific mate finding signals covary with fitness in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Since virgin females must reduce the risk of remaining unmated, we hypothesized virgin females to signal more or for longer than mated females, which we confirmed in this study. A higher signaling rate of virgin compared to mated females has previously been found in other Heliothine moths, such as the corn earworm Helicoverpa zea (Kingan et al, 1993 ), the subflexus straw Chloridea (Heliothis) subflexa (Blankers et al, 2021 ), and the Pyralid Indian meal moth Plodia interpunctella (Brady & Smithwick, 1968 ). These intuitive findings support the notion that virgin signaling females put more effort into mate attraction effort compared to mated females to increase their chance for mating.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Since virgin females must reduce the risk of remaining unmated, we hypothesized virgin females to signal more or for longer than mated females, which we confirmed in this study. A higher signaling rate of virgin compared to mated females has previously been found in other Heliothine moths, such as the corn earworm Helicoverpa zea (Kingan et al, 1993 ), the subflexus straw Chloridea (Heliothis) subflexa (Blankers et al, 2021 ), and the Pyralid Indian meal moth Plodia interpunctella (Brady & Smithwick, 1968 ). These intuitive findings support the notion that virgin signaling females put more effort into mate attraction effort compared to mated females to increase their chance for mating.…”
Section: Discussionmentioning
confidence: 69%
“…In the closely related moth C . subflexa , a lower percentage of females was found calling in the night after mating, however, calling effort increased to about 50% again in subsequent nights (Blankers et al, 2021 ). The fact that mated females continue to signal emphasizes that both sexes may benefit from mating multiply (Blankers et al, 2021 ; Gao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic mapping studies have revealed several QTL underlying difference in sex pheromone composition in H. subflexa and even a single conversion step in the biochemical pathway, such as from Z11-16:OH to Z11-16:OAc, could be catalyzed by multiple enzymes (Groot et al, 2013). In addition, variation in pheromone composition in H. subflexa is explained by fitness variation (Blankers et al, 2021), indicating many different genetic factors likely contribute small additional fractions to the total variance. Another explanation comes from population genetics: re-orientation of genetic covariances in response to bottlenecks may free up additive genetic variance, thereby paradoxically increasing levels of genetic variance (Carson, 1990; Templeton, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, sex pheromones can vary between and within populations (e.g. Bacquet et al, 2016; Groot et al, 2009; Pelozuelo et al, 2004; Vereecken et al, 2007), and even within individuals (Blankers et al, 2021), and can be equally important for mate assessment and choice (De Pasqual et al, 2021; Johansson & Jones, 2007; Steiger & Stökl, 2014).…”
Section: Introductionmentioning
confidence: 99%